Differences in the Activity of Endogenous Bone Morphogenetic Protein Signaling Impact on the Ability of Induced Pluripotent Stem Cells to Differentiate to Corneal Epithelial‐Like Cells. (21st December 2017) - Kamarudin, Taty Anna; Bojic, Sanja; Collin, Joseph; Yu, Min; Alharthi, Sameer; Buck, Harley; Shortt, Alex; Armstrong, Lyle; Figueiredo, Francisco C.; Lako, Majlinda
Abstract: Cornea is a clear outermost layer of the eye which enables transmission of light onto the retina. The transparent corneal epithelium is regenerated by limbal stem cells (LSCs), whose loss/dysfunction results in LSCs deficiency (LSCD). Ex vivo expansion of autologous LSCs obtained from patient's healthy eye followed by transplantation onto the LSCs damaged/deficient eye, has provided a successful treatment for unilateral LSCD. However, this is not applicable to patient with total bilateral LSCD, where LSCs are lost/damaged from both eyes. We investigated the potential of human induced pluripotent stem cell (hiPSC) to differentiate into corneal epithelial‐like cells as a source of autologous stem cell treatment for patients with total bilateral LSCD. Our study showed that combined addition of bone morphogenetic protein 4 (BMP4), all trans‐retinoic acid and epidermal growth factor for the first 9 days of differentiation followed by cell‐replating on collagen‐IV‐coated surfaces with a corneal‐specific‐epithelial cell media for an additional 11 days, resulted in step wise differentiation of human embryonic stem cells (hESC) to corneal epithelial progenitors and mature corneal epithelial‐like cells. We observed differences in the ability of hiPSC lines to undergo differentiation to corneal epithelial‐like cells which were dependent on the level of endogenous BMP signaling and could be restored via the activation of this signaling pathway by a specific transforming growth factor β inhibitor (SB431542). Together our data reveal a differential ability of hiPSC lines to generate corneal epithelial cells which is underlined by the activity of endogenous BMP signaling pathway. Stem Cells 2018;36:337–348 Abstract : Schematic diagram showing that addition of bone morphogenetic protein 4 (BMP4), epidermal growth factor, and retinoic acid to the culture media of differentiating human induced pluripotent stem cell (hiPSC) results, followed by replating in collagen IV and supplementation with CnT‐PR and FBS, results in differentiation to corneal epithelial progenitor and cells. Nonresponsive hiPSC lines characterized by low endogenous activity of BMP signaling pathway need an additional SB431542 supplementation step to differentiate into corneal epithelial cells.